How Happy are They? Assessing Patron Satisfaction in Reference Delivery through a Continuous, Brief Survey. Issue 3 (2nd October 2021) - Bischoff, Marissa; Wages, B.; Robb, C.
ABSTRACT: Measuring the quality of service delivery in an academic library presents challenges, particularly in relation to reference training and supervision. In early 2020, the Harold B. Lee Library at Brigham Young University implemented a short, three-question survey to monitor patron satisfaction in two areas of the library, the Religion and Family History and the Social Science help desks. This survey revealed patrons reflect positively on the delivery of services in these areas. Trainings related to the mission of the organization, empathy, journey mapping, experience planning, and RUSA guidelines were given to the student employees and volunteers staffing the areas. There was not a measurable improvement in service delivery in the short term as a result of the customer service training implemented during the 6-week survey span, but the trainings were still deemed valuable and important. This survey model was successful in providing instantaneous feedback, measuring a baseline of customer satisfaction in our areas, showing trends in service quality, and providing qualitative data from patrons.